1994
DOI: 10.2165/00002512-199404010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Streptokinase

Abstract: Streptokinase has been administered to many thousands of elderly patients with acute myocardial infarction. Results of large, randomised trials provide convincing evidence that intravenous streptokinase confers a distinct survival benefit in this population subgroup following myocardial infarction. The placebo-controlled ISIS-2 study demonstrated a 5-week absolute mortality reduction of 38 per 1000 patients aged 60 to 69 years administered streptokinase, compared with only 16 per 1000 for patients aged less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Like the blood coagulation pathway, the fibrinolytic pathway involves the sequential activation of trypsin-like serine proteases. The conversion of plasminogen to plasmin is the final step in the fibrinolytic pathway; plasmin is the protease responsible for the lysis of blood clots ( , ). This conversion involves proteolysis at the Arg561−Val562 bond of plasminogen; the new N-terminal amino group is believed to form a salt bridge with the carboxylate of Asp740 in a manner analogous to the activation of trypsinogen to trypsin () (chymotrypsinogen numbering, Table ).…”
mentioning
confidence: 99%
“…Like the blood coagulation pathway, the fibrinolytic pathway involves the sequential activation of trypsin-like serine proteases. The conversion of plasminogen to plasmin is the final step in the fibrinolytic pathway; plasmin is the protease responsible for the lysis of blood clots ( , ). This conversion involves proteolysis at the Arg561−Val562 bond of plasminogen; the new N-terminal amino group is believed to form a salt bridge with the carboxylate of Asp740 in a manner analogous to the activation of trypsinogen to trypsin () (chymotrypsinogen numbering, Table ).…”
mentioning
confidence: 99%
“…The possible mechanism of hypotension is bradykinin mediated vasodilatation with peripheral pooling of the blood and this effect may be beneficial in patients of AMI presented acute heart failure. In some studies it was observed that the in hospital mortality was slightly lower in patients of AMI with acute heart failure receiving SK infusion [17].…”
Section: Discussionmentioning
confidence: 99%